How does the use of Complementary Therapies contribute to the experience of patients with breast cancer? - Perkins, Katy Michelle (2013)
Purpose The prevalence of Complementary and Alternative Medicines (CAMs) amongst breast cancer patients has been well documented within the literature. The nature of CAMs has made it difficult to determine their contribution to patient’s experiences using quantitative research. This review aims to identify qualitative studies looking at the role of CAMs for breast cancer patients. Methods A systematic literature review approach was used. Studies were identified through rigorous searching of online databases and hand searching references. The results of these studies were synthesised into key themes using meta-ethnography to form conclusions. Results Eight studies were identified using inclusion/exclusion criteria. These results were synthesised to form 5 key themes. These are the decision to use, the relationship between Orthodox Health Care Professionals and CAM use, the effectiveness of CAMs, the barriers to using CAM and the implications for future healthcare. Conclusions This review concluded that there are a plethora of reasons why people decided to use CAMs. Participants reported that CAMs were effective in treating physical side effects of conventional medicine. However more importantly, they were effective at making them feel better. Orthodox Health Care Professionals were often identified as expressing negative views towards CAMs and many women wanted their physician to support their CAM use and help provide information and advice. Drawing this literature together may give Orthodox Health Care Professionals a better understanding of these issues. Relevance This review has helped to collate qualitative data and shed light as to why breast cancer sufferers chose to use CAMs and their effectives. These results can be used to clarify an area where the literature is often quite confusing and disputed. Further research is required into whether the results of the study could be feasibly implemented into the clinical environment.